Weaning Food Formulation from Different Blends of Cereals and Legumes - Balla Elhardallou, Sirelkhatim (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
Six weaning food formulations F 1 —F 6 composed of wheat (50-55 % ) de-hulled broad beans (15-35 %), sesame (5-10 %), fenugreek (0- I5 %), skim milk (0-8 %), sugar (4 %), ground nut oil (1.5 %) and vitamins/salt mixture (l .5 %); were selected for calculated amino acid scores and energy values. They were processed using the roller drum- drying technique. Protein content of processed formulations F l -F 6 was found in the range of 17.4 to 18.5% and energy value from 346 to 372 Kcal/100g. Viscosity at 12.5 % guel concentration ranged from 2600 to 8350 cp for F 5 and F3 respectively. The high viscosity ofF 3 can be related to its fenugreek content (15 %). Weaning food formulations including wheat, de-hulled broad beans and sesame with fenugreek at zero and 5% level showed acceptable characteristics and high nutritive value.